Konsekuensi Yuridis Pelaku Plagiasi Terhadap Pemegang Hak Cipta Urban Light di Taman Rabbit Town Kota Bandung: Studi Kasus Putusan Perkara Nomor 31/Pdt.Sus-Hak Cipta/2020/Pn.Niaga.Jkt.Pst - Wibowo, Sigit (Jurnal Hukum Caraka Justitia, 2025)
The purpose of this study is to determine and analyze the form of legal consequences for perpetrators of criminal plagiarism against the copyright holder “Urban Light” against the manager of Rabbit Town Park, who plagiarized his work. This research uses normative legal research methods that are prescriptive, which is a method by examining library materials shown in written regulations. The approach methods used in this legal writing are the case approach and the statutory approach. The result of the study is the existence of legal consequences for the perpetrators of plagiarism of a work of authorship, which has legal consequences for them. The perpetrators of plagiarism in this case were imposed legal sanctions in the form of civil sanctions with the payment of compensation. This legal sanction was decided by the Judge, as a legal remedy taken by the other party harmed, namely the copyright holder Urban Light, because his work has been plagiarized by the management of Rabbit Town Park without permission for his copyright. The basis of the lawsuit brought by the copyright holder is the existence of moral rights and economic rights inherent in the copyright holder, which are normatively regulated in the Copyright Act. Manifestation of copyright is a creation that arises automatically based on the declarative principle after the creation is realized in a real creation without reducing restrictions according to the norms in the legislation.